2022
DOI: 10.1002/cbin.11885
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from bone marrow mesenchymal stromal cells of severe aplastic anemia patients attenuate hematopoietic functions of CD34+ hematopoietic stem and progenitor cells

Abstract: Mesenchymal stromal cells (MSC) regulate hematopoiesis in the bone marrow (BM) niche and extracellular vesicles (EVs) released by BM-MSC are important mediators of the cross-talk between BM-MSC and hematopoietic stem and progenitor cells (HSPC). We have previously demonstrated that BM-MSC of severe aplastic anemia (SAA) patients have an altered expression of hematopoiesis regulatory molecules. In the present study, we observed that CD34 + HSPC when cocultured with BM-MSC EVs from aplastic anemia patients exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Additionally, pathways analysis showed enrichment of several pathways such as apoptosis, MAPK, PI3K/Akt, mTOR, chemokine receptor signalling, etc., which are crucial for maintaining hematopoietic homeostasis 42 . Our findings here provide with an insight that miRNAs enriched in AA BM-MSC EVs could potentially dampen HSPC functions in the microenvironment through impediment of these pathways, which is in alignment with our previous finding where we showed that AA BM-MSC EVs promoted apoptosis in healthy HSPC 25 . Concomitantly, our in-silico analysis of miRNA-mRNA interaction revealed that these EV miRNAs targeted 235 HSPC genes and their pathways analysis showed significant enrichment of pathways involved in cell survival and cell death.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Additionally, pathways analysis showed enrichment of several pathways such as apoptosis, MAPK, PI3K/Akt, mTOR, chemokine receptor signalling, etc., which are crucial for maintaining hematopoietic homeostasis 42 . Our findings here provide with an insight that miRNAs enriched in AA BM-MSC EVs could potentially dampen HSPC functions in the microenvironment through impediment of these pathways, which is in alignment with our previous finding where we showed that AA BM-MSC EVs promoted apoptosis in healthy HSPC 25 . Concomitantly, our in-silico analysis of miRNA-mRNA interaction revealed that these EV miRNAs targeted 235 HSPC genes and their pathways analysis showed significant enrichment of pathways involved in cell survival and cell death.…”
Section: Discussionsupporting
confidence: 92%
“…BM-MSC are the key cells of the BM microenvironment that supports HSPC functions by direct cell contact and paracrine release of growth factors and EVs 5,6,1316 . We have previously demonstrated that BM-MSC EVs from AA patients hamper the proliferative, colony-forming capacity and enhance apoptosis of HSPC 25 . However, the exact mechanism by which AA BM-MSC EVs exert their functional effect on HSPC is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MSCs can effectively regulate hematopoiesis, particularly in preventing the replacement of BM hematopoietic cells by adipocytes in patients with AA. MSCs also improve the hematopoietic microenvironment, and promote BM hematopoiesis; therefore, maintenance of a normal number and optimal activity of MSCs is essential for the recovery of hematopoietic function (Srivastava et al 2022 ).…”
Section: Clinical Strategies For Improving Terc Function Via Cell Rep...mentioning
confidence: 99%